Exogenous cinnamic acid alleviates salinity-induced stress in sweet pepper (Capsicum annuum L.) seedlings. Issue 3 (2nd July 2020) - Lin, Chien-Yau; Chung, Hsiao-Hang; Kuo, Chun-Teh; Yiu, Jinn-Chin
ABSTRACT: The underlying mechanism of mediation of plant salt tolerance by cinnamic acid (CA) is unclear. We aimed to investigate the influence of exogenously applied CA on the growth, antioxidant system, and ionic balance of sweet pepper under salinity stress. A set of sweet pepper seedlings was pretreated with 150 mM NaCl for 2 days. Then, 50 μM exogenous CA was applied, and the seedlings were allowed to grow for 7 more days while subject to salinity treatment every other day. The vegetative parameters, photosynthetic characteristics, nitric oxide (NO) signalling, ion leakage, antioxidant capacity, and ion contents were measured. Decreased Na + and Cl − contents and reduced lipid peroxidation were observed after application of CA, resulting in improved photosynthesis through upregulation of the antioxidant system and proline accumulation. CA regulated the antioxidant system by increasing the activities of antioxidant enzymes and influenced the concentrations of nonenzymatic antioxidants (flavonoids). Increased NO and enhanced cyclic guanosine monophosphate biosynthesis were observed in CA-treated plants. CA treatment elevates NO and flavonoid content, enhances antioxidant activity, alleviates lipid peroxidation, and increases proline level and K + /Na + ratio in salt-stressed plants. Exogenous CA could be considered as an economical practice for enhancing sweet pepper performance under salt conditions.